2016
DOI: 10.4269/ajtmh.15-0318
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Persistent Chikungunya Virus RNA but not Infectious Virus in Experimental Vertical Transmission in Aedes aegypti from Malaysia

Abstract: Abstract. Vertical transmission may contribute to the maintenance of arthropod-borne viruses, but its existence in chikungunya virus (CHIKV) is unclear. Experimental vertical transmission of infectious clones of CHIKV in Aedes aegypti mosquitoes from Malaysia was investigated. Eggs and adult progeny from the second gonotrophic cycles of infected parental mosquitoes were tested. Using polymerase chain reaction (PCR), 56.3% of pooled eggs and 10% of adult progeny had detectable CHIKV RNA, but no samples had dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…CHIKV viral RNA (but not viable virus) in artificially infected Aedes aegypti has been previously reported by Wong et al [29]. In contrast Vazeille et al reported on the absence of vertical transmission of the East/Central/South African (ECSA) strain of the virus in Aedes albopictus in their studies of experimental infections [35].…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 80%
See 1 more Smart Citation
“…CHIKV viral RNA (but not viable virus) in artificially infected Aedes aegypti has been previously reported by Wong et al [29]. In contrast Vazeille et al reported on the absence of vertical transmission of the East/Central/South African (ECSA) strain of the virus in Aedes albopictus in their studies of experimental infections [35].…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 80%
“…Experimental evidence of TOT of CHIKV was debated in the 1980s [30], but has been repeatedly observed in laboratory settings with Aedes spp. (S1 Table) [27][28][29][31][32][33][34]. The isolation of https://doi.org/10.1371/journal.pntd.0008362.g003 Table 3.…”
Section: Discussionmentioning
confidence: 99%
“…aegypti , wherein a persistent CHIKV RNA detection was reported in the mosquito eggs and adults progeny. However, it was not proven to be viable and infectious virus, omitting the possibility of the vertical transmission for CHIKV in Aedes sp 57. Nonetheless, we cannot exclude the limitation for using the quantitative PCR for virus detection as the RNA viral copy number can give an overestimation of infectious viral particles.…”
Section: Discussionmentioning
confidence: 95%
“…Nonetheless, we cannot exclude the limitation for using the quantitative PCR for virus detection as the RNA viral copy number can give an overestimation of infectious viral particles. Given the high sensitivity of real-time PCR in detecting the region encoding for E1 protein of CHIKV,57 even a slight contamination of virus nucleic acid on the surface of the organs (from tissue beside the organs) would have been sufficient to prime the RT-PCR reaction and hence yielding the overestimation of the infection percentage in the secondary organs including salivary glands.…”
Section: Discussionmentioning
confidence: 99%
“…albopictus exhibits high potential for vertical transmission which makes them a suitable candidate to maintain dengue virus infection in a population . However, detection of virus genome by qPCR may not indicate the presence of infectious virus as previously shown with chikungunya virus . In view of two recent studies from Malaysia and India , where natural vertical transmission of dengue virus to Ae.…”
Section: Discussionmentioning
confidence: 99%